Pendampingan Kepada Masyarakat Tentang Pre Eklamsia Pada Ibu Hamil Di Puskesmas Kassi-Kassi Kota Makassar - Fitriani Fitriani; Hasiba hasiba; Ayu ayu (Pusat Riset dan Inovasi Nasional, 2022)
preeclampsia is one of the most common medical problems that occurs during pregnancy, and is the main cause of maternal death in the world and in indonesia, therefore it is very important for pregnant women to be trained about the condition during pregnancy and learn appropriate self-care to prevent and control its occurrence. Preeclampsia. However, there are still pregnant women and people who do not have the knowledge and skills about the danger signs of preeclampsia, efforts to treat and prevent preeclampsia. So this service activity is carried out to teach and assist pregnant mothers about pre-eclampsia so that their knowledge increases and they can prevent pre-eclampsia. The method in this activity is a pre-test before carrying out the activity of providing information related to pre-eclampsia, then continuing with the post-test to see the success of the activity. The results of the activities of 13 targets who experienced preeclampsia showed that there were 11 pregnant women with good knowledge and 2 pregnant women with poor knowledge after providing counseling and assistance. This indicates that pregnant women with preeclampsia have more good knowledge after assistance